The Effect of Sonic Activation Tip Placement and Root Canal Irrigants On Smear Layer Removal - Karnady, Josephine Amanda; Iskandar, Bernard Ongki; Prahasti, Anastasia Elsa; Sjahruddin, Loes Djimahit (Odonto : Dental Journal, 2025)
Background: Root canal preparation produces smear layer. Smear layer removal is mandatory before obturation, which could be achieved by using root canal irrigants such as EDTA 17% and maleic acid 7%. As reported in previous research, irrigant solutions combined with sonic irrigation systems can remove the smear layer. This study aims to assess the effectiveness of irrigation solution with sonic activation tip placement at 2 mm and 4 mm from working length within 30 seconds in eliminating the smear layer in the apical third of the root canal.Method: 120 extracted single-rooted premolars decoronated and prepared with reciprocating file (#25/06), then randomly divided into six groups for final irrigation. Group 1: EDTA 17% + activation tip 2 mm from working length, Group 2: Maleic acid 7% + activation tip 2 mm from working length, Group 3: Distilled water + activation tip 2 mm from working length, Group 4: EDTA 17% + activation tip 4 mm from working length, Group 5: Maleic acid 7% + activation tip 4 mm from working length, Group 6: Distilled water + activation tip 4 mm from working length. Teeth were split into half using chisel and mallet and observed by Scanning Electron Microscope with 1000x magnification.Result: Kruskal-Wallis test showed significant differences among the groups (p<0.001).Conclusion: Sonic activation tip placement influences the cleanliness of the apical third of the root canal